Randomised, double-blind, placebo-controlled, cross-over single dose study of the bronchodilator duration of action of combination fluticasone furoate/vilanterol inhaler in adult asthma. (October 2016) - Braithwaite, Irene; Williams, Mathew; Power, Sharon; Pilcher, Janine; Weatherall, Mark; Baines, Amanda; Moynihan, Jackie; Kempsford, Rodger; Beasley, Richard; ,
Abstract: Background: Fluticasone furoate (FF)/vilanterol (VI) is a once-daily maintenance treatment for asthma and chronic obstructive pulmonary disease. The duration of bronchodilation beyond 24 h has not been determined previously. Methods: Adults aged 18–65 (n = 32), with asthma and reversibility to salbutamol (≥15% and ≥200 mL increase in forced expiratory volume in 1 s [FEV1 ]) participated in a double-blind, placebo-controlled, crossover study. Patients were admitted to a clinical trials unit for 72 h, and inhaled, in random order, placebo or FF/VI 100/25 mcg via ELLIPTA dry powder inhaler on two occasions 7–14 days apart. FEV1 was measured at baseline, 15 and 30 min, 1, 2, 4, 12, 24, 36, 48, 60, and 72 h. The differences in change in FEV1 from baseline between treatments and corresponding two-sided 95% confidence intervals (CI) were calculated at each time point. Findings: FF/VI produced a rapid onset of bronchodilation (adjusted mean difference in change from baseline in FEV1 versus placebo at 15 min, 252 mL [95% CI 182–322]). Maximum bronchodilation was observed at 12 h (adjusted mean difference in the change from baseline in FEV1, 383 mL [95% CI 285–481]). Bronchodilation was maintained throughout the 72-h assessment period (adjusted mean difference in the change in FEV1 from baseline at 72 h, 108 mL (95% CI 15–200]). FF/VI was well tolerated and no serious side effects were reported. Interpretation: A single dose of FF/VI 100/25 mcg showed evidence of a 72-h bronchodilator duration of action in adults with asthma. Graphical abstract: A single dose of FF/VI 100/25mcg achieves 72 h bronchodilator duration of action in patients with asthma. Highlights: A single-dose of FF/VI 100/25 mcg provides a 72-h bronchodilator duration of action. FF/VI provides rapid onset of bronchodilation, with a maximum effect at 12 h. The duration of FF/VI bronchodilation is sufficient to enable once-daily dosing. If a dose is missed, FF/VI provides sufficient bronchodilator effect for one more day.